A Quasi-Brittle damage model in the framework of Bond-based Peridynamics with Adaptive Dynamic Relaxation method - H. N. Yakin; N. Nikabdullah; M. R. M. Rejab (Journal of Mechanical Engineering and Sciences, 2021)
Peridynamics (PD) is a new tool, based on the non-local theoryfor modelling fracture mechanics, where particles connected through physical interaction used to represent a domain. By using the PD theory, damage or crack in a material domain can be shown in much practicalrepresentation. This study comparesbetween Prototype Microelastic Brittle (PMB) damage model and a new Quasi-Brittle (QBR) damage model in the framework of the Bond-based Peridynamics (BBPD) in terms of the damage plot.An in-house codeusing Matlab was developedfor BBPD with inclusion of both damage models, andtested for a quasi-static problem with the implementation ofAdaptive Dynamic Relaxation (ADR) methodin the theoryin order to get a faster steady state solutions. This paper is the first attempt to include ADR method in the framework of BBPD forQBR damage model. This paperanalyseda numerical problem with the absence of failure and comparedthe displacement with literature result that usedFinite Element Method (FEM). The obtained numerical results are in good agreement with the result from FEM. The same problemwas used withtheallowanceof the failure to happen for both of the damage models; PMB and QBR, to observe the damage pattern between these two damage models.PMBdamage model produced damage value of roughly twice compared to the damage value from QBRdamage model.It is found that the QBR damage model with ADR under quasi-static loading significantly improves the prediction of the progressive failure process, and managed to model a more realistic damage model with respect to the PMB damage model.